An actor prepares. Reprint. - Stanislavski (Bloomsbury revelations., 2013)
This book is the most famous acting training book ever to have been written and the work of Stanislavski has inspired generations of actors and trainers. This translation was the first to introduce Stanislavski's 'system' to the English speaking world and has stood the test of time in acting classes to this day. Stanislavski here deals with the inward preparation an actor must undergo in order to explore a role to the full. He introduces the concepts of the 'magic if' units and objectives, of emotion memory, of the super-objective and many more now famous rehearsal aids. Now available in the 'Bloomsbury Revelations' series to mark the 150th anniversary of Stanislavski's birth, this is an essential read for actors, directors and anyone interested in the art of drama.